Transcription factor co‐occupied regions in the murine genome constitute T‐helper‐cell subtype‐specific enhancers. Issue 11 (21st September 2015) - Fang, Zhuo; Hecklau, Katharina; Gross, Fridolin; Bachmann, Ivo; Venzke, Melanie; Karl, Martin; Schuchhardt, Johannes; Radbruch, Andreas; Herzel, Hanspeter; Baumgrass, Ria
Abstract : Transcription factors (TFs) regulate cell‐type‐specific gene expression programs by combinatorial binding to cis ‐genomic elements, particularly enhancers, subsequently leading to the recruitment of cofactors, and the general transcriptional machinery to target genes. Using data integration of genome‐wide TF binding profiles, we defined regions with combinatorial binding of lineage‐specific master TFs (T‐BET, GATA3, and ROR‐γt) and STATs (STAT1 and STAT4, STAT6, and STAT3) in murine T helper (Th) 1, Th2, and Th17 cells, respectively. Stringently excluding promoter regions, we revealed precise genomic elements which were preferentially associated with the enhancer marks p300 and H3K4me1. Furthermore, closely adjacent TF co‐occupied regions constituted larger enhancer domains in the respective Th‐cell subset (177 in Th1, 141 in Th2, and 266 in Th17 cells) with characteristics of so‐called super‐enhancers. Importantly, 89% of these super‐enhancer regions were Th‐cell subtype‐specific. Genes associated with super‐enhancers, including relevant Th‐cell genes (such as Ifng in Th1, Il13 in Th2, and Il17a in Th17 cells), showed strong transcriptional activity. Altogether, the discovered catalog of enhancers provides information about crucial Th‐cell subtype‐specific regulatory hubs, which will be useful for revealing cell‐type‐specific gene regulation processes.